Expansive Type Rational Contraction in Metric Space and Common Fixed Point Theorems - Yadav, Devnarayan; Tiwari, Surendra Kumar (Mikailalsys Journal of Mathematics and Statistics, 2023)
The field of expansive mappings in fixed-point theory is one of the most fascinating areas in mathematics. In this theory, contraction is one of the main tools used to prove a fixed point's existence and uniqueness. For all of the analyses, the fixed point theorem proposed by Banach's contraction theory is highly popular and widely used to prove that a solution to the operator equation Tx=x exists and is unique. Through the present article, we utilize rational expressions in metric spaces to deliver unique common stable (fixed) point results in expansive mapping. The main outcomes of numerous relevant innovations in the newest research are built upon them.